Capital Intensity, Inventory Intensity, Leverage, and Tax Aggressiveness: CSR as a Moderator in Consumer Goods Companies - Mohammad Hafis Zaenal; Jamaluddin Majid; Della Fadhilatunisa (Academic Bright Collaboration, 2026)
Tax aggressiveness is a crucial issue in corporate governance in Indonesia because it directly impacts state revenue and corporate legitimacy in the eyes of stakeholders. Differences in corporate financial characteristics, particularly capital intensity, inventory intensity, and leverage, are thought to influence a company's tendency to manage its tax obligations. This study aims to analyze the effect of capital intensity, inventory intensity, and leverage on tax aggressiveness and examine the role of Corporate Social Responsibility (CSR) as a moderating variable. This study uses a quantitative approach with secondary data obtained from annual reports and sustainability reports of consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The study sample consisted of 80 observations selected using a purposive sampling method. Hypothesis testing was conducted using multiple linear regression analysis and Moderated Regression Analysis (MRA). The results show that capital intensity, inventory intensity, and leverage have a significant effect on tax aggressiveness. Furthermore, CSR disclosure is proven to strengthen the influence of inventory intensity and weaken the influence of capital intensity and leverage on tax aggressiveness. These findings indicate that CSR acts as a governance mechanism capable of moderating the relationship between corporate financial characteristics and tax aggressiveness. The primary contribution of this research is providing empirical evidence that CSR functions not only as a corporate social responsibility but also as a control instrument in corporate tax strategies in Indonesia.